PROMOTING THE STUDENTS’ AUTONOMY LEARNING: NEWS PROGRAM, AN OUT-OF-SPEAKING CLASS ACTIVITY - Puspitarini, Ika (Erudio Journal of Educational Innovation, 2018)
This paper presents the result of the pilot project of an out-of-class; it is the making of a news program with 20-25 minutes duration. The pilot project took place at UIN Malulana Malik Ibrahim Malang; it was conducted benefitted from the familiarity of the young people toward social media. The aims of this task were to promote the students’ autonomy learning by giving them the opportunities to practice their speaking skill, building up their self-confidence, and challenging their creativity. Therefore, the questionnaire, as the self-reflection feedback, consisted of three questions; whether the making of news program gives them the opportunities to practice their speaking skill, builds up their confidence, and challenges their creativity. There were 30 students involved in this pilot project. The result of data analysis showed that most of the participants strongly agreed the making a new program give them a chance to practice their speaking skill, build up their self-confidence, and challenge their creativity. Therefore, making a news program can be an out-of-speaking class activity in order to promote the students’ autonomy learning.